2015
DOI: 10.1002/bip.22618
|View full text |Cite
|
Sign up to set email alerts
|

d‐amino carboxamide‐based recruitment of dinitrophenol antibodies to bacterial surfaces via peptidoglycan remodeling

Abstract: During the past few decades there has been a rapid emergence of multidrug resistant bacteria afflicting human patients. At the same time, reduced output from pharmaceutical industry in this area precipitated a sharp decrease in the approval of new antibiotics. The combination of these factors potentially compromises the ability to effectively combat bacterial infections. While traditional drug discovery efforts continue in the pursuit of small molecule agents that disrupt bacterial growth, non-traditional effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
(77 reference statements)
0
28
0
Order By: Relevance
“…During active stages of infection, bacterial cell walls come in direct contact with their human hosts, a feature that can be exploited by the immune system in detecting and eradicating these pathogens (Kieser and Kagan, 2017; Royet, et al, 2011). We have recently demonstrated that synthetic cell wall building blocks can metabolically label the surface of Gram-positive bacteria with antigenic epitopes (Fura, et al, 2016; Fura and Pires, 2015; Fura, et al, 2014; Fura, et al, 2017). In turn, grafting of haptens onto bacterial cell surfaces triggered the recruitment of endogenous antibodies (pools of existing antibodies in humans).…”
Section: Introductionmentioning
confidence: 99%
“…During active stages of infection, bacterial cell walls come in direct contact with their human hosts, a feature that can be exploited by the immune system in detecting and eradicating these pathogens (Kieser and Kagan, 2017; Royet, et al, 2011). We have recently demonstrated that synthetic cell wall building blocks can metabolically label the surface of Gram-positive bacteria with antigenic epitopes (Fura, et al, 2016; Fura and Pires, 2015; Fura, et al, 2014; Fura, et al, 2017). In turn, grafting of haptens onto bacterial cell surfaces triggered the recruitment of endogenous antibodies (pools of existing antibodies in humans).…”
Section: Introductionmentioning
confidence: 99%
“…23 The difficulty in finding new efficacious antibiotics against S. aureus highlights the need to explore less conventional therapeutic approaches such as antibiotic adjuvants or immunotherapies. [24][25][26][27][28][29] For example, adjuvants can potentiate antibiotics by improving their accessibility to their cognate molecular targets. Likewise, anti-infective immunotherapeutics (e.g., antibody recruiting agents developed by our lab [24][25][26][27]29 ) work by targeting specific macromolecules on bacterial cell surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is most commonly observed in skin infections but it can cause more severe internal infections. 11,12 According to the Centers for Disease Control and Prevention (CDC), hard-to-treat methicillin resistant strains of S. aureus (MRSA) infect an estimated 120,000 people and cause ∼20,000 deaths a year in the United States alone. The difficulty in finding new efficacious antibiotics against S. aureus highlights the need to explore less conventional therapeutic approaches such as antibiotic adjuvants or immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in finding new efficacious antibiotics against S. aureus highlights the need to explore less conventional therapeutic approaches such as antibiotic adjuvants or immunotherapies. [10][11][12][13][14][15] For example, adjuvants can potentiate antibiotics by improving their accessibility to their cognate molecular target. Likewise, anti-infective immunotherapeutics (e.g., antibody recruiting agents developed by our lab [10][11][12][13]15 ) work by targeting macromolecules on bacterial cell surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation